Towards new modes of knowledge exchange for sustainability transformations: an exploration of multi-sited dialogue as conferencing practice - Blane Harvey; Ying-Syuan (Elaine) Huang; Bruce Goldstein; Nick Graham (Global Social Challenges Journal)
Actors working on global climate and sustainability challenges are faced with two competing imperatives: first, there is an ever-expanding body of knowledge, networks and initiatives generating new insights that should be shared. Second, we see a growing recognition that fly-in, fly-out conferencing practices are an insufficient and unsustainable model for learning, boundary crossing and collaboration towards sustainability transformations. Against this backdrop, we argue that knowledge exchange for societal transformations needs to consider three interrelated dimensions: (1) equity and inclusion – access to and representation in both process and content for all, (2) low carbon – limits the ecological burden produced by the exchange, and (3) impact – outcomes at individual and collective levels that enhance our ability to act. How we navigate the tensions that may emerge from these dimensions is a matter of pressing importance. This research article examines the potential of multi-sited dialogues as an approach to co-producing transdisciplinary solutions by using the three dimensions as the analytical framework. We report on a series of dialogue-focused conference sessions convened at three international conferences in 2023. Our findings describe the contributions that the multi-sited dialogue process brought to knowledge co-production across space and time, and the contribution of facilitation practices to the outcomes of these dialogues. We also introduce and discuss the set of principles for transforming sustainable conferencing practices that were co-produced over the three dialogues.